Treatment of the knife edge mandibular alveolar ridge using ridge splitting - Dorottya Pénzes; Fanni Simon; Eitan Mijritsky; Orsolya Németh; Márton Kivovics (Hungarian Dental Association, 2022)
Alveolar atrophy following tooth extraction is a common limitation of rehabilitation with dental implant-borne prosthesis. Direction, rate, and degree of the atrophy shows significant differences in the jaws. Patients frequently present with a knife-edge ridge in the molar and premolar regions of the mandible. Numerous techniques have been described for the horizontal augmentation of the alveolar ridges. Tatum has described ridge splitting to restore bone width prior to implant placement. The aim of our case presentation is to describe a modified approach to ridge splitting. Osteotomies in the recipient site were carried out using a piezoelectric surgical device to mobilize the buccal cortical bone. An autologous bone block harvested from the retromolar region of the mandible was applied as a spacer between the buccal and lingual cortical plates. The block graft was stabilized by osteosynthesis screws. After a 3-month healing period, excellent bone regeneration was observed clinically with perfect ossification in the osteotomy sites. Upon re-entry the augmented area was sufficiently widened to accommodate implants according to the prosthetic plan. Two dental implants were placed in the augmented bone submerged. The submerged of the implants was uneventful. Within the limitations of our studies this novel approach of ridge splitting is a safe and effective method to restore the width of the alveolar ridge.